STABILITY AND ANTIBACTERIAL ACTIVITY TEST OF NANOSILVER BIOSYNTHETIC HYDROGEL - ERMAWATI, DIAN EKA; YUGATAMA, ADI; RAMADHANI, BERLIANA RIZKA; PERTIWI, INTAN; ROSIKHOH, ANISWATUN; NOVACHIRIA, SAFIRA RAHMA (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aims to formulate nanosliver (AgNPs) biosynthetic hydrogel for topical antibacterial treatment and its stability and antibacterial activity. Methods: The mixture (Silver nitrate solution and Turmeric juice) was stirred at room temperature for 24 h; afterward, it was analyzed using UV-VIS spectrophotometry, particle size analysis, and TEM. The carbopol 940 was selected as a gelling agent with an AgNPs concentration of 5%, 10%, 20%, and 30%. Furthermore, the gel preparation was tested for stability using the cycling test method and antibacterial activity. The antibacterial activity against Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, and Pseudomonas aeruginosa. Results: The nanosilver biosynthetic has a yellow-brown color with the maximum wavelength peak at 433 nm, and a particle size of 157.4-166.7 nm. TEM analysis showed that AgNPs have a round shape, while the antibacterial activity of hydrogel preparations was moderately inhibited. Furthermore, the hydrogel was evaluated for pH, viscosity, dispersibility, and antibacterial activity before-after the cycling test. Formula with 30% AgNPs is chosen formula with pH value of 5.87±0.65; viscosity of 4833.3±2.82 c. Ps; and dispersibility of 5.50±0.15 after cycling test. Conclusion: The high concentration of AgNPs will increase the viscosity, pH, and dispersibility. Formula with 30% AgNPs have the highest antibacterial activity. Furthermore, all hydrogel preparations meet the requirements of Indonesian Standard Product (SNI) No. 06-2588-1992 for good gel stability before and after the cycling test.